The The Effect of Auditor Competence, Audit Complexity, and Auditor Time Budget Pressure on Audit Quality with The Information System Understanding as Moderating Variable - Risya Khaerun Nisa, Risya Khaerun Nisa (Journal of Accounting Inquiry, 2022)
Purpose: The progress of a company can be seen from the position of its financial statements. Therefore the financial statements must be audited by a qualified Public Accountant or Auditor to show that the financial statements are presented fairly. The auditor must perform a quality audit to provide reliable and trustworthy information. This study aims to determine the effect of auditor competence, audit complexity, and auditor time budget pressure on audit quality with the information systems understanding as moderating variable. Methodology: This study conducted on auditors working at the Public Accounting Firm of DKI Jakarta recorded in the directory of Indonesian Institute of Accountants. The samples of this study consists of 20 Public Accounting Firm. Data collection technique used primary data. Primary data obtained through the survey by distributing questionnaires to respondents. The questionnaires were distributed directly to the auditors at 20 Public Accounting Firm. Data analysis technique used moderated regression analysis (MRA). Findings: The result of the research shows that: Auditor competence has a positive effect on audit quality, audit complexity does not effect audit quality, and auditor time budget pressure has negative effect on audit quality. The interaction of information system understanding between auditor competence with audit quality is an independent variable. The interaction of information system understanding between audit complexity with audit quality is not a moderation variable. Meanwhile, the interaction of information system understanding between auditor time budget pressure with audit quality is a quasi moderator. Novelty: This paper uses auditor competence that distinguishes it from previous studies. Keywords: auditor competence, audit complexity, auditor time budget pressure, audit quality, information system understanding